IMPLEMENTATION APPROACH SCIENTIFIC FOR INCREASE PERFORMANCE STUDY STUDENT SUBJECT - Husen, Choirun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The aim of this study was to improve student achievement at class X senior high school of Sullamul Hidayah Probolinggo by using a scientific approach contains observations, giving questions, exercise, reasoning and communication. This research was a classroom action research conducted collaboratively between researcher and subject teachers of PPKn at class X. The subjects of research were students at class X senior high school of Sullamul Hidayah Probolinggo. the numbers of students were 30 pupils with heterogeneous capabilities. the research was conducted in two cycles, each cycle consists of two meetings. The technique of collecting data was used through observation, documentation and learning achievements tests. In this research used a qualitative approach and PTK (Classroom Action research) research methods, and used observation, interviews and documentation US techniques of data collections. The results showed that the achievement of PPKn at class X senior high school increased then before. it was proven from the aspects of the student participation in giving opinions, cooperation and finishing the task. The results of the PPKn subjects test were the numbers of students who passed were 25 students (83%). It was met the minimum of competency standards that are used in senior high school of Sullamul Hidayah Probolinggo.